Towards Formal Specification of PaperLess Office Systems - Bambang Nurcahyo Prastowo; Jazi Eko Istiyanto; Ahmad Ashari; Khabib Mustofa (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2015)
Abstract—The Center for Information and CommunicationTechnology Services of Gadjah Mada University runs a kind offormal office communication system called PLO (stands forPaperLess Office). Developed to serve ad hoc needs of the center,the system evolves for several years without properdocumentation. Several attempt store write the system failed dueto the lack of the documentations. Judging from the fact that it hasbeen serving the institution well for several years, the system canbe treated as a user requirement. A formal specification is writtenbased on it.Keywords—formal specification; paperless office; informationsystem